Students' and Teachers' Perception on Reward in Online English Teaching Context - Saraswati, N.M.S.D.; Ratminingsih, N.M.; Utami, IG.A.L.P. (Journal of Education Reseach and Evaluation, 2020)
Rewarding is one of the factors that influence student learning outcomes so it is important to describe the reward given by the teacher, the teacher's perception of the reward and the student's perception of the reward given by the teacher. This qualitative study aimed to investigate the types of rewards used in teaching English online; frequency of rewarding by teachers in online learning; in what context the reward is given and for what purpose; how teachers perceive rewards in online learning; and how students perceive rewards in online classrooms. The subjects of this study were 116 people consisting of 112 first grade students and 4 first grade teachers. To collect data, there were 3 methods used, namely: observation, recording and taking note. Meanwhile, the main instrument was the researcher himself who was assisted by additional instruments, questionnaires and observation sheets. The collected data were analyzed qualitatively with the Miles and Hubberman model. The results of this study are 1) the teacher gives verbal and object rewards, 2) verbal rewards are more often given, 3) there are three contexts of giving rewards, namely: perfect, almost perfect and needs improvement with different goals, 4) teacher perceptions show giving rewards have a positive influence in academic and non-academic students and 5) students' perceptions of rewards are that they are very happy and motivated after receiving a reward. These results have implications for designing rewards to be diverse and creative to motivate students.